Coplanar Waveguide Fed Circularly Polarized Notch Band Antenna with Defected Ground Structure - P Poorna Priya; Habibulla Khan; B T P Madhav (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
A compact printed wideband antenna with circular polarization is designed and the antenna parameters are analyzed in this work. Finite Element method based HFSS tool is used to design and simulate the antenna model. A basic structure of rectangular monopole is converted into a trapezoidal shape with tapered step ground. Different iterations of radiating element as well as defected ground structures are examined in this work to analyze the circular polarization characteristics of the antenna. A peak realized gain of 4.3dB and peak directivity of 3.8dB is attained from the current designed models. The design models are optimized and prototyped on FR4 substrate for measurement validation. By incorporating Split ring resonator (SRR) notch band characteristics are attained in the proposed wideband antenna.